(untitled) (Research, Society and Development, 2020)
The vast natural reserve of the cerrado biome features exotic and little-known fruit species, such as guapeva (Pouteria gardneriana Radlk), of great biological and nutritional value. Objective of the work was to optimize the extraction process of guapeva antioxidant compounds, with varying concentrations of hydrochloric acid at different contact times, using the response surface analysis (ASR) method. For the extraction of antioxidant compounds, a central rotational compound design (DCCR) was adopted with the use of acetone / methanol solvents, and different concentrations of HCl (0.2 mol / l, 0.3 mol / l, 0.4 mol / l 0.5 mol / l and 0.6 mol / l) and different contact times in minutes (15, 30, 60, 90 and 105) using 4 central points. The DPPH total antioxidant activity was evaluated by the DPPH method according to Rufino et al., (2009) and the determination of total phenolics according to Waterhouse (2002). The readings were performed on a spectrophotometer at 515 nm. The STATISTICA 8.0 software was used. for the determination of analysis of variance, Regression Analysis and Response Surface. With the ASR, it was found that the optimum working range for optimizing the extraction of antioxidant compounds in the guapeva pulp was the HCl concentration of 0.50 mol / L, with the contact time variable not relevant. In the peel, the optimum range was above 0.50 mol / L of HCL, with a contact time of less than 30 minutes. For the total phenolic compounds of both parts of the fruit, they obtained an optimum range of 0.40 mol / L of HCL in 60 minutes of contact. The experiment proved to be an important method to optimize and build predictive models, with acidification by HCl varying the contact time.